2017
DOI: 10.1007/s11356-017-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moso bamboo (Phyllostachys edulis) invasions on soil nitrogen cycles depend on invasion stage and warming

Abstract: Plant invasions may alter soil nutrient cycling due to differences in physiological traits between the invader and species they displace as well as differences in responses to anthropogenic factors such as nitrogen deposition and warming. Moso bamboo is expanding its range rapidly around the world, displacing diverse forests. In addition, near expansion fronts where invasions are patchy, moso bamboo and other species each contribute soil inputs. Nitrogen transformations and greenhouse gas (GHG) emissions are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 61 publications
2
19
1
Order By: Relevance
“…The increased soil available P (this study) and N (Li et al 2017a) due to the invasion by moso bamboo could further promote the invasion of moso bamboo into C. japonica stands, which may partly explain the accelerated expansion of moso bamboo observed across its native range.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The increased soil available P (this study) and N (Li et al 2017a) due to the invasion by moso bamboo could further promote the invasion of moso bamboo into C. japonica stands, which may partly explain the accelerated expansion of moso bamboo observed across its native range.…”
Section: Discussionmentioning
confidence: 75%
“…2015). In addition, recent studies have also reported that moso bamboo invasion affected physical, chemical, and biological soil properties (Lin et al 2014;Fukushima et al 2015;Shinohara and Otsuki 2015;Chang and Chiu 2015;Xu et al 2015;Wang et al 2016b;Song et al 2017;Li et al 2017a;Qin et al 2017;Shiau and Chiu 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, nutrient management in forest ecosystems should consider the ecological effects of fertilization under the context of global climate change, considering the potential interactions among global change factors [93,94], nutrient input [95], and internal element cycling within forest ecosystems [96][97][98][99][100][101]. For example, in plantations experiencing intensive management, N input may induce more N leaching due to excessive application, especially in areas characterized by acid soils [101,102].…”
Section: Resultsmentioning
confidence: 99%